2019
DOI: 10.21037/jtd.2019.08.86
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 ameliorates alveolar fluid clearance disturbance in lipopolysaccharide-induced lung injury via aquaporin 5 and MAPK signaling pathway

Abstract: Background: A characteristic of acute lung injury (ALI) is the inflammatory damage of alveolar fluid transport. Lipoxins are endogenous lipids involving in the resolution of inflammation. It is found that lipoxin A4 (LXA4) has the distinct properties to improve the anti-edema and pro-resolution function in inflammation. Since aquaporins (AQPs) have essential roles in the integrity of barrier function during fluid transport, especially AQP5 in the maintaining of the epithelium permeability, the current study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…The LXA 4 receptor FPR2 has been identified; the properties and distribution of the receptor are known, and we are now starting to appreciate the complex intracellular signal transduction events post-LXA 4 receptor activation, which appear to be cell type-dependent. A recent study demonstrated that LXA 4 regulates the MAPK signaling pathway via inhibition of the phosphorylation of p38 and JNK in the airway . Tabas and colleagues have provided the first evidence that MerTK signaling pathways are mobilized to produce LXA 4 in macrophages .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LXA 4 receptor FPR2 has been identified; the properties and distribution of the receptor are known, and we are now starting to appreciate the complex intracellular signal transduction events post-LXA 4 receptor activation, which appear to be cell type-dependent. A recent study demonstrated that LXA 4 regulates the MAPK signaling pathway via inhibition of the phosphorylation of p38 and JNK in the airway . Tabas and colleagues have provided the first evidence that MerTK signaling pathways are mobilized to produce LXA 4 in macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that LXA 4 regulates the MAPK signaling pathway via inhibition of the phosphorylation of p38 and JNK in the airway. 138 Tabas and colleagues have provided the first evidence that MerTK signaling pathways are mobilized to produce LXA 4 in macrophages. 139 In addition, 15-epi-LXA 4 suppresses PI3K/ AKT signaling pathway to regulate TNF-α-induced tissue factor in vascular endothelial cells.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…LXA4 was found to enhance CFTR expression in AT-II cells damaged by LPS treatment through downregulation of Akt phosphorylation, which led to improved AFC[ 96 ]. LXA4 also increases the expression of α and γ subunits of ENaC channel[ 97 ], and AQP5 in LPS-stimulated epithelial cells[ 98 , 99 ], which contribute to enhanced fluid clearance, improved gas exchange, and pulmonary edema resolution during lung injury. LXA4 improves the integrity of the epithelial barrier by upregulating the expression of junction proteins such as zona occludens 1, claudin 1, and occludin[ 100 ].…”
Section: Mscs Promote Repair Of Tissue Damagementioning
confidence: 99%
“…Lipoxine A4 (LXA4) a braking signal in inflammatory response reduced the severity of inflammation and restored alveolar fluid clearance via upregulation of AQP5 in LPS induced lung tissue exhibiting its pro-resolution and anti- edematic activity in alleviating ALI [36] . Inhibition of NF-κB activation by fasudil a selective Rho- kinase (ROCK) inhibitor in LPS induced lung injury restored the expression of AQP5 resulting in predominant reduction in lung water content and pulmonary edema formation [37] .…”
Section: Aquaporin Modulators In Lung Inflammation and Edema: Promisimentioning
confidence: 99%